Аналіз індикаторів сталого розвитку міської пасажирської транспортної системи - Кристопчук, М. Є.; Krystopchuk, M. (ЦНТУ, 2021)
Проведено аналіз результатів досліджень функціонування пасажирської транспортної системи громадського транспорту міста Рівне в розрізі розвитку принципів сталої міської мобільності. Використання системи індикаторів сталого розвитку міської пасажирської транспортної системи дозволяє провести оцінку поточної ситуації в місті та окреслити перспективні напрямки удосконалення системи громадського транспорту у взаємозв’язку з просторовим розвитком міських територій з метою забезпечення комфортного пересування мешканців для задоволення трудових та культурно-побутових пересувань. Establishing the main attributes of population mobility is one of the most important indicators of urban development, which has been studied by domestic and foreign scientists for use in the practice of urban transport planning and the development of sustainable transport systems. Mobility characteristics are also an important source and result for the development of changes in the city master plan and the creation of new management decisions in the operation and operation of the route network of urban passenger transport. However, at the present stage of implementation of transport studies of urban population movement requires consideration of indicators of sustainable development of urban transport systems. In this regard, a study of the functioning of the passenger transport system of public transport in the city of Rivne in terms of the development of the principles of sustainable urban mobility. The use of the system of indicators of sustainable development of urban passenger transport system allows to assess the current situation in the city and outline promising areas for improving the public transport system in conjunction with the spatial development of urban areas to ensure comfortable movement of residents to meet labor and cultural movements. The questionnaire "Study of mobility of the population in the city of Rivne" was used as initial data for definition of indicative indicators of functioning of passenger transport system of public transport of the city of Rivne, in the context of its sustainable development. Three indicative parameters are taken into account, namely: the indicator of access to mobility services, the indicator of the possibility of active mobility and the indicator of the level of satisfaction with public transport. Based on the calculated values of indicative indicators, it can be argued that some indicators of sustainable urban mobility for the city of Rivne are of mediocre importance. This indicates the need to develop strategic measures to improve the city's public passenger transport system in conjunction with its spatial development to increase the comfort of movement of residents of all groups.
Analysis of Indicators of Sustainable Development Urban Passenger Transport System
Keywords: міський пасажирський транспорт; транспортна система; сталий розвиток; індикативні показники; матриця пасажирських кореспонденцій; ефективність; urban passenger transport; transport system; sustainable development; indicative indicators; matrix of passenger correspondence; efficiency